Monitoring trafficking and expression of hemagglutinin-tagged transient receptor potential melastatin 4 channel in mammalian cells - Hwang, Eun Mi; Lee, Bo Hyun; Byun, Eun Hye; Lee, Soomin; Kang, Dawon; Lee, Dong Kun; Song, Min Seok; Hong, Seong-Geun (대한약리학회, 2023)
The TRPM4 gene encodes a Ca2+-activated monovalent cation channel called transient receptor potential melastatin 4 (TRPM4) that is expressed in various tissues. Dysregulation or abnormal expression of TRPM4 has been linked to a range of diseases. We introduced the hemagglutinin (HA) tag into the extracellular S6 loop of TRPM4, resulting in an HA-tagged version called TRPM4-HA. This TRPM4-HA was developed to investigate the purification, localization, and function of TRPM4 in different physiological and pathological conditions. TRPM4-HA was successfully ex-pressed in the intact cell membrane and exhibited similar electrophysiological prop-erties, such as the current-voltage relationship, rapid desensitization, and current size, compared to the wild-type TRPM4. The presence of the TRPM4 inhibitor 9-phen-anthrol did not affect these properties. Furthermore, a wound-healing assay showed that TRPM4-HA induced cell proliferation and migration, similar to the native TRPM4. Co-expression of protein tyrosine phosphatase, non-receptor type 6 (PTPN6 or SHP-1) with TRPM4-HA led to the translocation of TRPM4-HA to the cytosol. To investigate the interaction between PTPN6 and tyrosine residues of TRPM4 in enhancing chan-nel activity, we generated four mutants in which tyrosine (Y) residues were substi-tuted with phenylalanine (F) at the N-terminus of TRPM4. The YF mutants displayed properties and functions similar to TRPM4-HA, except for the Y256F mutant, which showed resistance to 9-phenanthrol, suggesting that Y256 may be involved in the binding site for 9-phenanthrol. Overall, the creation of HA-tagged TRPM4 provides researchers with a valuable tool to study the role of TRPM4 in different conditions and its potential interactions with other proteins, such as PTPN6.